Highly parallel lab evolution reveals that epistasis can curb the evolution of antibiotic resistance - Marta Lukačišinová (Nature Portfolio, 2020)
The antibiotic resistance crisis calls for new ways of restricting the ability of bacteria to evolve resistance. Here, Lukačišinová et al. perform highly controlled evolution experiments in E. coli strains to identify genetic perturbations that strongly limit the evolution of antibiotic resistance through epistasis.